Assessing water security in Sub-Saharan Africa in the context of climate change threats: a case study - Timothy O. Ogunbode; Victor O. Oyebamiji; Ayobami A. Oyelami; Timothy A. Akinkuolie; Aruna O. Adekiya; Paul I. Ifabiyi (International Journal of Climate Change Strategies and Management, 2025)
Purpose – This paper aims to investigate water security in Iwo, Nigeria, located in the sub-Saharan region, within the broader context of climate change threats and contributes insights towards achieving the Sustainable Development Goal 6 (SDG 6) targets by 2030. It unravels the interplay between climate change, demographics and water dynamics, employing meticulous surveys and climatic analyses. The study identifies critical patterns and urges urgent action through evidence-based recommendations. By evaluating household water use and predictive models, the research guides stakeholders towards strategic interventions. The overarching goal is to prompt proactive measures for enhanced water justice, aligning with SDG 6, and fostering global dialogue on sustainable water management in similarly challenged regions. Design/methodology/approach – The investigation employs a multifaceted methodology: a 12-month survey (937 households) assesses water sources and usage; climatic data (31 years) from the Nigeria Meteorological Agency identifies trends. Descriptive and inferential statistical analyses unravel patterns. Demographic assessments illuminate key factors, notably the prevalent involvement of female heads. Regression analysis also unveils predictive capabilities. This comprehensive approach, integrating surveys, climatic data analysis and statistical tools, ensures a nuanced understanding of water security dynamics in Iwo, Nigeria. Findings – This study on water security in Iwo, Nigeria, reveals climate change threats jeopardizing national water accessibility goals by 2030. Surveying 937 households, it finds a predominantly domestic water use pattern, with significant reliance on female heads and individuals above 18. Climatic data analysis indicates water loss during dry and previously rainy months, confirming climate change impacts. Household water use consistently exceeds supply, falling below WHO recommendations. Regression analysis identifies significant predictive models, emphasizing the need for urgent efforts to enhance water accessibility and align with SDG 6 targets. Research limitations/implications – Limitations of this research include potential model inadequacy (indicated by low R values), suggesting the need for additional variables for better predictive accuracy. The study’s focus on a specific region, Iwo, Nigeria, may limit generalizability to broader contexts. The reliance on self-reported data from households introduces the possibility of response bias, impacting the accuracy of findings. Furthermore, the study’s duration (12 months) may not fully capture long-term trends, and the exclusive use of climatic data from a single national agency may overlook nuanced local variations. These limitations highlight areas for future research refinement and expansion. Practical implications – Practical implications of this research underscore the urgency of addressing climate change-induced threats to water security, especially in regions like Iwo, Nigeria. The findings emphasize the need for targeted interventions to enhance water accessibility, considering the predominance of domestic usage. Policymakers should prioritize sustainable water management strategies, considering climatic variations, and actively involve communities in decision-making. The identification of predictive models signals the potential for effective planning and resource allocation. Overall, the study highlights the imperative for immediate, intentional efforts to ensure just and sustainable water access, aligning with SDG 6 targets, particularly in agrarian communities facing climate-related challenges. Social implications – The research’s social implications are significant, reiterating a predominantly female and adult population involved in water-related activities in Iwo, Nigeria. The findings highlight the domestic nature of water use, reflecting the area’s agrarian character. The identified water accessibility challenges underscore potential socio-economic disparities. Urgent interventions are needed to ensure equitable access, aligning with Sustainable Development Goal 6. Policymakers should consider the socio-demographic dynamics uncovered, emphasizing community involvement in crafting solutions. Addressing these social aspects is crucial for fostering resilience in the face of climate change and promoting sustainable, just water practices in the region. Originality/value – The research offers original contributions by specifically assessing water security in Iwo, Nigeria, in view of the prevailing global climate change Climate change projections. Original elements include a year-long survey of 937 households, incorporating climatic data spanning three decades. The study identifies a predominantly female and adult involvement in water-related activities, emphasizing the agrarian nature of the region. The revelation of predictive models and the examination of water use patterns contribute novel insights. These original aspects enhance our understanding of localized challenges, providing a basis for targeted interventions. Overall, the research adds unique perspectives to the discourse on water security and climate resilience in the studied region.